Same-sex marriage conundrum in Nigeria: the conflict of laws dimension (2015)
The changing concept of the proper parties to marriage has been having its toll on the national and international jurisprudence of marriage. The orthodox concept of marriage is predicated on a relationship between man and woman, which has attached to it some legal implications. However, the concept of marriage is now taking a new dimension as to the parties who may legally contract such a relationship in some jurisdictions, which results in the much touted same-sex marriage. Same-sex marriage is relatively a new phenomenon in marriage jurisprudence and has been creating some upheavals in the legal terrain nationally and internationally, especially in the region of conflict of laws. The main purpose of this research is to review the Nigerian disposition to same-sex unions and the attendant conflict of laws problems that may arise as a result of the stance taken on the unions.